ASFMR1 splice variant: A predictor of fragile X-associated tremor/ataxia syndrome. (August 2018) - Vittal, Padmaja; Pandya, Shrikant; Sharp, Kevin; Berry-Kravis, Elizabeth; Zhou, Lili; Ouyang, Bichun; Jackson, Jonathan; Hall, Deborah A.
Abstract : Objective: To explore the association of a splice variant of the antisense fragile X mental retardation 1 ( ASFMR1 ) gene, loss of fragile X mental retardation 1 ( FMR1 ) AGG interspersions and FMR1 CGG repeat size with manifestation, and severity of clinical symptoms of fragile X-associated tremor/ataxia syndrome (FXTAS). Methods: Premutation carriers (PMCs) with FXTAS, without FXTAS, and normal controls (NCs) had a neurologic evaluation and collection of skin and blood samples. Expression of ASFMR1 transcript/splice variant 2 ( ASFMR1 -TV2), nonspliced ASFMR1, total ASFMR1, and FMR1 messenger RNA were quantified and compared using analysis of variance. Least absolute shrinkage and selection operator (LASSO) logistic regression and receiver operating characteristic analyses were performed. Results: Premutation men and women both with and without FXTAS had higher ASFMR1 -TV2 levels compared with NC men and women (n = 135, 135, p < 0.0001), and ASFMR1 -TV2 had good discriminating power for FXTAS compared with NCs but not for FXTAS from PMC. After adjusting for age, loss of AGG, larger CGG repeat size (in men), and elevated ASFMR1 -TV2 level (in women) were strongly associated with FXTAS compared with NC and PMC (combined). Conclusions: This study found elevated levels of ASFMR1-TV2 and loss of AGG interruptions in both men and women with FXTAS. Future studies will be needed to determine whether these variables can provide useful diagnostic or predictive information.